Synchrotron radiation analysis of root dentin: the roles of fluoride and calcium ions in hydroxyapatite remineralization - Nutthapong Kantrong; Krassawan Khongkhaphet; Nutnicha Sitornsud; Pakaporn Lo-apirukkul; Waraporn Phanprom; Catleya Rojviriya; Penphitcha Amonpattaratkit; Watcharaphong Ariyakriangkai (Journal of Synchrotron Radiation, 2022)
Although the use of fluoride for root caries control is reported to be effective, the mechanism of maintaining hydroxyapatite is still unclear. This study elucidates the roles of fluoride in the recrystallization of hydroxyapatite, and the impact of calcium to maintain the abundance of hydroxyapatite on acid-challenged root dentin with a novel approach – using synchrotron radiation. Root dentin samples obtained from 40 extracted human premolars were subjected to pH challenge in combination with fluoride treatment. The effect of fluoride on hydroxyapatite regeneration on the root was investigated by using a range of fluoride concentrations (1000–5000 p.p.m.) and the EDTA-chelation technique in vitro. Synchrotron radiation X-ray micro-computed tomography and X-ray absorption spectroscopy were utilized to characterize the chemical composition of calcium species on the surface of prepared samples. The percentage of hydroxyapatite and the relative abundance of calcium species were subsequently compared between groups. The absence of calcium or fluoride prevented the complete remineralization of hydroxyapatite on the surface of early root caries. Different concentrations of fluoride exposure did not affect the relative abundance of hydroxyapatite. Sufficient potency of 1000 p.p.m. fluoride solution in promoting hydroxyapatite structural recrystallization on the root was demonstrated. Both calcium and fluoride ions are prerequisites in a caries-prone environment. Orchestration of F− and Ca2+ is required for structural homeostasis of root dentin during acid attack. Sustainable levels of F− and Ca2+ might thus be a strict requirement in the saliva of the population prone to root caries. Fluoride and calcium contribute to structural homeostasis of tooth root, highlighting that routine fluoride use in combination with calcium replenishment is recommended for maintaining dental health. This study also demonstrates that utilization of synchrotron radiation could provide a promising experimental platform for laboratory investigation especially in the dental material research field.